2017
DOI: 10.1124/jpet.116.239665
|View full text |Cite
|
Sign up to set email alerts
|

Selexipag Active Metabolite ACT-333679 Displays Strong Anticontractile and Antiremodeling Effects but Lowβ-Arrestin Recruitment and Desensitization Potential

Abstract: Prostacyclin (PGI 2 ) receptor (IP receptor) agonists, which are indicated for the treatment of pulmonary arterial hypertension (PAH), increase cytosolic cAMP levels and thereby inhibit pulmonary vasoconstriction, pulmonary arterial smooth muscle cell (PASMC) proliferation, and extracellular matrix synthesis. Selexipag (Uptravi, 2-{4-[(5,6-diphenylpyrazin-2-yl)(isopropyl)amino]-butoxy}-N-(methylsulfonyl)acetamide) is the first nonprostanoid IP receptor agonist, it is available orally and was recently approved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…In accordance with these observations, the results of the present in vitro study showed that in cultured SSc skin fibroblasts/myofibroblasts, ACT-333679 induced the same effects as selexipag, but at a concentration three times lower than that of the parent compound (selexipag 3 μM and 0.3 μM, ACT-333679 1 μM and 0.1 μM). The concentrations of selexipag and especially ACT-333679 were in accordance with several in vitro studies [ 15 , 24 26 ]. Moreover, the lowest ACT-333679 concentration (0.1 μM) is in range with the values of its bioavailability which were well-tolerated by the HSs and were indicated by the area under the curve during a dose interval of administration (AUC t ), as reported in several studies [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In accordance with these observations, the results of the present in vitro study showed that in cultured SSc skin fibroblasts/myofibroblasts, ACT-333679 induced the same effects as selexipag, but at a concentration three times lower than that of the parent compound (selexipag 3 μM and 0.3 μM, ACT-333679 1 μM and 0.1 μM). The concentrations of selexipag and especially ACT-333679 were in accordance with several in vitro studies [ 15 , 24 26 ]. Moreover, the lowest ACT-333679 concentration (0.1 μM) is in range with the values of its bioavailability which were well-tolerated by the HSs and were indicated by the area under the curve during a dose interval of administration (AUC t ), as reported in several studies [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 89%
“…The fibroblasts isolated from the biopsy sample from each patient with SSc were independently cultured up to 80% of confluence and then maintained in serum-free medium for 4 h. After starvation, a portion of these cells was maintained in growth medium at 5% of FBS without treatment (untreated cells) and another portion was treated for 48 h with three different concentrations of selexipag (30 μM, 3 μM, or 0.3 μM); a further portion of cells was treated for 48 h with three different concentrations of ACT-333679 (10 μM, 1 μM or 0.1 μM) (Actelion Pharmaceutics, Switzerland), in accordance with recent studies [ 15 , 24 26 ].…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Mechanistic and functional differences between prostanoid and non-prostanoid IP agonists are now beginning to emerge that need to be carefully considered in a clinical context. Both ralinepag and MRE-269 behave as partial agonists in cAMP assays in CHO cells stably expressing the human IP receptor and in human PASMCs from PAH patients [35,37,38]. Partial agonism may in part explain why MRE-269 was about 65-fold less potent than iloprost at inhibiting contractions in human pulmonary arteries [19] and why selexipag has little overall effect on platelet aggregation in vivo [39].…”
Section: Development Of Prostacyclin Mimetics and Their Diverse Pharmmentioning
confidence: 99%
“…Because this did not happen, it might suggest either a large IP receptor reserve (redundancy) in the system and/or that IP function recovers sufficiently well in culture before agonist treatment. Other studies have suggested that partial agonism leads to limited β-arrestin recruitment and less IP receptor internalisation, and hence a lower likelihood of receptor desensitisation with MRE-269 compared to other analogues [38]. Against this notion, MRE269 still remains the weakest anti-proliferative agent when compared to other prostacyclin analogues in the same assay [37].…”
Section: Downregulation Of Ip Receptors In Pahmentioning
confidence: 99%